Regulation and activity-dependence of N-cadherin, NCAM isoforms, and polysialic acid on chick myotubes during development (The Rockefeller University Press, 1993)
Muscle development in vivo involves a complex sequence of cell-cell interactions in which secondary myotubes first form in association with primary myotubes and subsequently separate from them. We show here that during this process N-cadherin and the different structural forms of NCAM are regulated in a pattern that involves both temporal changes in expression and localization to particular regions of the muscle cell surface. In particular, levels of N-cadherin on maturing myotubes are decreased, and the form of NCAM synthesized by the muscle changes from a transmembrane non-polysialylated to a lipid-linked polysialylated membrane protein. Moreover, while NCAM was distributed on all myotube surfaces, the polysialyated form of NCAM was restricted to regions of the myotube surface that had recently separated from neighboring cells. We previously found that blockade of nerve-induced activity by d- Tubocurarine perturbed muscle cell interactions, resulting in a failure of myotubes to separate. We now show that this activity blockade also alters adhesion molecule expression. First, N-cadherin was no longer down-regulated in maturing myotubes, and its persistence on the surfaces of mature myotubes may partly explain their failure to separate. Secondly, the developmental switch from transmembrane to lipid-linked NCAM did not occur, and polysialylated NCAM was no longer formed. As the unusual physical properties of PSA have been proposed to impede cell-cell interactions, this alteration would also be expected to compromise cell separation. Together, these results suggest that the regulated expression of both N-cadherin and NCAM isoforms including their polysialylation, is an essential mechanism for the normal separation of secondary myotubes from primary myotubes.